The face of the brand: Spokesperson facial width‐to‐height ratio predicts brand personality judgments. Issue 8 (13th April 2022) - Deska, Jason C.; Hingston, Sean T.; DelVecchio, Devon; Stenstrom, Eric P.; Walker, Ryan J.; Hugenberg, Kurt
Abstract: Brands often employ spokespersons to serve as the face of their organization and spokespersons characteristics can influence consumer behavior. We examined whether a subtle, appearance‐based aspect— facial width‐to‐height ratio (fWHR)—affects brand judgments. Specifically, we demonstrate that high (low) fWHR spokespersons are more effective for rugged (sincere) brands leading to more positive ad evaluations, greater brand liking, and higher purchase intensions. Across four experiments, we used across‐target and within‐individual manipulations of spokesperson fWHR to test our hypotheses and investigate the downstream implications for consumer preferences and purchasing intentions. We find that spokesperson fWHR influenced judgments of spokesperson effectiveness for different kinds of brands (Study 1); spokesperson fWHR impacts a brand's perceived personality (Study 2); and that congruency between spokespersons' faces and brands' personalities influence how much consumers like brands, their advertisements, and how willing they are to purchase advertised products (Studies 3–4). This study has implications for marketers and contributes to the brand personality and person perception literatures by demonstrating how subtle variations in spokespersons' face structure can influence consumer judgments.